Measurement of customers’ satisfaction among e-commerce users towards the logistics service quality of courier service in Sabah - Nur Faizilah Rizal; Sidah Idris (International Journal of Business, Economics and Law, 2024)
The rapidly increasing popularity of e-commerce especially in Sabah, Malaysia put pressure on logistics services to respond to the increasing customer demands. However, physical factors like geographical location, infrastructure, and service delivery constraints are major barriers that affect customer satisfaction in the region. This study investigates the relevance that exists between logistics service quality and customer satisfaction among e-commerce users in Sabah using SERVQUAL as the research model. The model evaluates five dimensions of service quality: tangibility, reliability, responsiveness, empathy and assurance. Data was gathered using structured questionnaires from 192 respondents. The results indicate that both assurance and empathy have a positive relationship with customer satisfaction implying that trust, profesionalism and personalized services contribute positively to the customer experience. On the other hand, tangibility, reliability, and responsiveness displayed a relatively weaker correlation, which posits that the customers’ decision-making process in this setting is mainly governed by emotional as well as interpersonal factors. In operational terms, it provides guidelines for logistics providers as to how to start delivering better services: employing and training employees so that the customer develops trust in the carrier; using technology to make the service more transparent; and finally dealing with regional delivery problems.